Characterisation of waste water and biochemical oxygen demand - Raffo Lecca, Eduardo (2014)
Water is the most important substance for human beings, after oxygen. Is a constituent of most animals and plants and is present in amount of minerals (Raffo Lecca, Treated Water And Peruvian Law, 2013). The BOD is one of the most important indicators in measuring pollution in wastewater, as well as in drinking water control.